Price-level Targeting versus Inflation Targeting in a Forward-looking Model - David Vestin (Sveriges Riksbank, 2000)
This paper examines a price-level target in a model with a forward-looking Calvo-Taylor Phillips curve. Contrary to conventional wisdom, it is found that price-level targeting leads to a better trade-off between inflation and output-gap variability than inflation targeting, when the central bank acts under discretion. In some cases, price-level targeting under dircretion results in the same equilibrium as inflation targeting under commitment.
Keywords: E52; E58; 330; Monetary policy; Price-level targeting; Inflation targeting